Clinico-dermatologic patterns of Paederus dermatitis in a teaching hospital, South India - Akila Kumaraguru; Rajalakshmi Ramalingam; Prabha Thangaraj; Rajanga Sekar Seethalakshmi; Narasimman Balasubramanian (Journal of Family Medicine and Primary Care, 2022)
Background: Paederus dermatitis (PD) is common skin condition occurring in South India caused due to contact with Rove beetle. It is often misdiagnosed due to wide difference in its presentation. The aim of this study was to describe the clinical, sociodemographic, and environmental condition of patient's presenting with PD. Methodology: A descriptive study was done among all patients diagnosed of PD at the Dermatology department of a teaching hospital in Trichy, South India, between January and December 2020. A detailed clinical history, examination of the lesion, and systemic examination was done. Patients were followed-up after 1 week to re-assess the lesion. A total of 117 cases were included in the final analysis. Results: The mean age of patients was 24.54 ± 11.8 years. Female were 51% with 84.6% residing in rural area. Majority of the cases presented between January and May. Presence of thick vegetation (85.5%) and sleeping with windows open (60.7%) were found to be the common risk factors. Most patients reported noticing the lesion in the morning with sudden onset associated with redness and tenderness with a bizarre pattern of lesion. Face, neck, and upper extremity were the most affected sites with burning sensation and itching, experienced by 82.1% and 76.1%, respectively. Ocular involvement with peri-orbital odema was seen among 17% of cases. Post-inflammatory pigmentation was present in 92.1% patients. Conclusion: PD present has a varying degree of skin lesions with absence of the typical linear pattern. Knowledge of its presentation is important to avoid misdiagnosis.